2015
DOI: 10.1186/s40555-015-0132-9
|View full text |Cite
|
Sign up to set email alerts
|

Biological mosquito control is affected by alternative prey

Abstract: Background: Mosquitofish were introduced to several countries of the tropics and subtropics as biological agents for the control of mosquito larvae. Meanwhile, they became a threat to native communities and fish worldwide, similar to other invasive species through resource competition, overexploitation, or habitat alteration. We investigated prey selectivity patterns of Gambusia affinis (mosquitofish) preying on larvae of the two Indian major carps (Catla catla and Labeo rohita) in the presence of varied propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 84 publications
1
11
0
1
Order By: Relevance
“…Goodsell and Kats () found that even when mosquito larvae are present, G. holbrooki prey on amphibian larvae to the same extent as when mosquito larvae are absent. This suggests that G. holbrooki follow, to some extent, the optimal foraging model (Werner and Hall, ; Kumar et al , ) which predicts that predators choose prey that minimize the energy used in foraging and optimize energy intake. Combining a stable isotope study with an estimation of abundance of each prey item in ponds would help to address this question.…”
Section: Discussionmentioning
confidence: 99%
“…Goodsell and Kats () found that even when mosquito larvae are present, G. holbrooki prey on amphibian larvae to the same extent as when mosquito larvae are absent. This suggests that G. holbrooki follow, to some extent, the optimal foraging model (Werner and Hall, ; Kumar et al , ) which predicts that predators choose prey that minimize the energy used in foraging and optimize energy intake. Combining a stable isotope study with an estimation of abundance of each prey item in ponds would help to address this question.…”
Section: Discussionmentioning
confidence: 99%
“…All experiments, including 5 replicates for each treatment, were conducted in 30 × 20 cm glass troughs containing 2 L autoclaved tap water. A series of short-term experiments was conducted to investigate the feeding rates of the mosquito fish following the protocol used by Kumar et al 57 . The initial density (Table 2 ) for each prey type and test duration was chosen based on preliminary feeding experiments such that at experimental termination a substantial number of prey remained unconsumed.…”
Section: Methodsmentioning
confidence: 99%
“…Complementary food switching in response to food scarcity has been observed in the zebra mussel (Dreissena polymorpha) that alternates between seston and detritus when access to phytoplankton is limited [91], as well as in Nile perch in Lake Victoria that switched from increasingly rare cichlids to aquatic invertebrates and other fish taxa [92]. Dramatic relaxation of food selectivity during periods of scarcity has also been observed in the rat (Rattus rattus) [12], macaque (Macaca fascicularis) [93,94], fox (Vulpes vulpes) [95], and mosquitofish (Gambusia affinis) [96].…”
Section: Trends Trends In In Ecology Ecology and Evolution Evolutionmentioning
confidence: 99%